STRENGTHENING LOCAL RIVER TRANSPORTATION (KLOTOK) AS RIVER TOURIST ATTRACTION - Mutiani, Mutiani; Putra, M. Adhitya Hidayat; Abbas, Ersis Warmansyah; Subiyakto, Bambang; Oktaviani, Ndaru Mukti (UNIVERSITAS PAKUAN, 2020)
Klotok as a river transportation mode is interesting to study. However, not much research focuses on how the role of klotok as a mode of transportation can attract tourists. Klotok becomes an icon as a river tourism icon because it presents a uniqueness for the audience. This study aims to describe how the role of klotok and its existence for the Banjar community. Interviews were conducted with three community groups, namely: klotok owners, traders, and visitors to the Siring Menara Pandang tourist destination. This is intended to provide a complete description of the function of klotok as a mode of water transportation, especially in river areas. The results of the study describe how klotok as a mode of water transportation is moored on the edge of the Martapura River, precisely Siring Menara Pandang. The choice of location is because Siring Menara Pandang is a public space that is used as well as a tourist destination. Revitalizing the river by prioritizing the river as a selling price to tourists has positioned klotok as a vital mode of transportation. Based on its development, klotok not only acts as a mode of river transportation but also as a choice of entertainment attractions for river tourism